2020
DOI: 10.1038/s41443-020-00380-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on pornography habits: a global analysis of Google Trends

Abstract: As the COVID-19 spread globally, social distancing, self-isolation/quarantine, and national lockdowns have become crucial to control the pandemic. However, these measures may also lead to increases in social isolation, loneliness, and stress, which can alter the consumption of pornography habits. The aim of the study was thus to explore the interest pattern in pornography and coronavirus-themed pornography during the COVID-19 outbreak. Google Trends® was employed to determine the most popular porn websites (Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 39 publications
3
73
1
12
Order By: Relevance
“…These increases in pornography use occurred in tandem with this same website offering a range of incentives for increased use. Similarly, analyses of internet search data suggested that interest in pornography peaked during the early stages of the pandemic (Zattoni et al, 2020). Collectively, this led to speculation in popular media (Grubbs, 2020) and peerreviewed journals (Király et al, 2020;Mestre-Bach et al, 2020;Sinclair et al, 2020) about the possibility for pornography use to increase over the course of the pandemic.…”
Section: Pornography In the Pandemicmentioning
confidence: 99%
“…These increases in pornography use occurred in tandem with this same website offering a range of incentives for increased use. Similarly, analyses of internet search data suggested that interest in pornography peaked during the early stages of the pandemic (Zattoni et al, 2020). Collectively, this led to speculation in popular media (Grubbs, 2020) and peerreviewed journals (Király et al, 2020;Mestre-Bach et al, 2020;Sinclair et al, 2020) about the possibility for pornography use to increase over the course of the pandemic.…”
Section: Pornography In the Pandemicmentioning
confidence: 99%
“…Pornhub has shared statistics on a regular basis revealing the changes and trends in the consumption of their content, showing a constantly positive deviation from average traffic on an average pre-pandemic day ( 42 ). A study employing Google Trends and joint point regression analysis demonstrated a significant rise (compared to last 4 years) in interest for pornographic websites in countries with “stay at home orders” ( 43 ).…”
Section: The Influence Of Covid-19 and The Lockdownmentioning
confidence: 99%
“…in a fixed timelapse. In this regard, the quantitative analysis of relative search volumes of pre-selected queries was used for several purposes during COVID-19 pandemic: 1) predicting COVID-19 cases ( Ahmad et al, 2020 ; Ayyoubzadeh et al, 2020 ; Jimenez et al, 2020 ; Mavragani and Gkillas, 2020 ; Sulyok et al, 2020 ; Venkatesh and Gandhi, 2020 ; Prasanth et al, 2021 ), 2) studying the web interest in COVID-19 ( Effenberger et al, 2020 ; Hu et al, 2020 ; Rovetta and Castaldo, 2020 ; Springer et al, 2020 ), 3) studying the adoption of infodemic terms and related consequences ( Cinelli et al, 2020 ; Cuan-Baltazar et al, 2020 ; Rovetta and Bhagavathula, 2020 ), 4) studying a full range of users’ psychological-emotional responses ( Husnayain et al, 2020 ; Rovetta and Castaldo, 2020 ; Zattoni et al, 2020 ; Brodeur et al, 2021 ; Zitting et al, 2021 ), 5) studying the impact of mass media and governmental policies on users’ web searches ( Rovetta and Bhagavathula, 2020 ; Sousa-Pinto et al, 2020 ; Huynh Dagher et al, 2021 ), 6) studying the economic-commercial impact ( Brodeur et al, 2021 ; Sotis, 2021 ), 7) studying the spread of COVID-19 symptoms ( Ahmad et al, 2020 ; Jimenez et al, 2020 ; Kluger and Scrivener, 2020 ; Walker et al, 2020 ), 8) studying other various web interests ( Berger et al, 2021 ; Elsaie and Youssef, 2021 ). This type of research is mainly based on the search for statistical cross-correlations between users’ web searches related to specific topics, such as symptoms, drugs, therapies, vaccines, number of infected people, number of deaths, anxiety, fear, stress, etc., and the number of disease contagions and deaths officially registered after a certain timespan.…”
Section: Introductionmentioning
confidence: 99%